DETERMINATION OF CHEMICAL STRUCTURE OF CYCLOLEHMANOSIDE A FROM ASTRAGALUS LEHMANNIANUS - A.A.Janibekov,; T.X.Naubeev,; N.Sh.Ramazanov,; G.A.Sabirova,; K.Dzh.Kucherbayev, (Academic Scientific Journal of Chemistry, 2019)
In the present work, the determination of chemical structure of the novel cycloartane glycoside, cyclolehmanoside A is given. Determination of chemical structure was carried out by using of chemical reaction (acidic hydrolysis) and spectral methods (1D and 2D NMR spectroscopy). Novel cycloartane glycoside, cyclolehmanoside A was isolated from aerial parts of Astragalus Lehmannianus Bunge (Leguminosae) by column chromatography on silica, and its chemical structure was established as 3-О-β-D-xylopyranoside, 6,16-di-О-β-Dglucopyranoside-24S-cycloartane-3β,6α,16β,24,25-pentaol.